2022
DOI: 10.2478/hukin-2022-000076
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance Tests, On-Ice Testing and Game Performance in Elite Junior Ice Hockey Players

Abstract: This study aimed to explore relationships between fitness, on-ice physical abilities and game performance among elite junior male ice hockey players. Twenty-one major junior ice hockey players (18.9 ± 1.4 years old) participated in the study. Measures including five fitness tests (anthropometric measures, pull up test, bench press test, broad jump, vertical jump) and three on-ice skating tests (multi-stage aerobic skating test, 44-m sprint test, and backward skating test) were assessed during their pre-season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…This indicates the importance of sprinting speed and acceleration in ice hockey performance. Even if these actions seem subsidiary in comparison with the total skating distance of 4,600-5,600 m (6,15), they are important for scoring goals, winning, or losing duels or even for the final outcome of the game (4,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the importance of sprinting speed and acceleration in ice hockey performance. Even if these actions seem subsidiary in comparison with the total skating distance of 4,600-5,600 m (6,15), they are important for scoring goals, winning, or losing duels or even for the final outcome of the game (4,15).…”
Section: Introductionmentioning
confidence: 99%
“…Studies including male and female college ice hockey players showed explained variance ranging from 4 to 55% examining the relationship between various maximum strength measures and on-ice linear sprint of various distances (6-44.8 m) (10,13,17,20). In addition, some studies showed 1-72% explained variance for off-ice performances (various jumps [loaded and unloaded/vertical and horizontal]) with on-ice linear sprint performances (6-55 m) at differing performance levels (youth, subelite, and professional) (4,5,10,14,16,17,20). However, more important for sports practice is whether these findings are also reflected in game performance.…”
Section: Introductionmentioning
confidence: 99%
“…The total distance covered during a game is about 4600 m, of which 2042 m is at high intensity in roughly 15 min [ 2 ]. Therefore, higher sprint performance in 10–30 m sprint seems to be correlated with higher playing level [ 3 , 4 ], leading to benefits in winning the puck [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneity in correlations could be due to large differences in study design and partially small sample sizes (high sampling error). Additionally, some studies show correlations of r = |0.09|-|0.85| for off-ice performances (different jumps [loaded and unloaded/vertical and horizontal]) with on-ice linear sprint (6–55 m) performances in different performance levels (youth, sub-elite and professional) [ 5 , 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing change of directional speed (COD) have been assessed in several sports disciplines, such as rugby ( Gabbett, 2006 ; Meir et al, 2001 ), soccer ( Maly et al, 2014 ; Sporis et al, 2010 ), and basketball ( Horicka and Simonek, 2019 ; Horníková and Zemková, 2022 ; Šeparović and Nuhanović, 2008 ); however, factors influencing COD in ice hockey have not been assessed. In ice hockey, COD studies ( Delisle-Houde et al, 2019 ; Gupta et al, 2022 ; Madden et al, 2019 ) have focused on the relationship between on-ice and off-ice scores ( Novák et al, 2019 ; Perez et al, 2021 ; Secomb et al, 2021 ; Wagner et al, 2021 ), performance levels ( Kokinda et al, 2012 ; Roczniok et al, 2016a ; Vigh-Larsen et al, 2021 ; Vigh-Larsen et al, 2020 ), or relationships between COD and match performance ( Daigle et al, 2022 ; Schwesig et al, 2021 ; Williams and Grau, 2020 ). Therefore, the structural basis of ice hockey COD, such as general off-ice conditions and anthropometric characteristics, remains unclear.…”
Section: Introductionmentioning
confidence: 99%